2008
DOI: 10.1007/s12144-008-9038-6
|View full text |Cite
|
Sign up to set email alerts
|

Parental Awareness and Monitoring of Adolescent Internet Use

Abstract: This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
100
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 25 publications
8
100
0
11
Order By: Relevance
“…The Byrne et al (2014) study did not find any effect of the child's gender on parent's underestimation of online risks. The Liau et al (2008) study found that parental knowledge about the adolescents' frequency of internet use was lowest among fathers with regard to their son's internet use. In all the other parent-child gender constellations, a comparable level of parental knowledge was found.…”
Section: Extent Of Parental Knowledgementioning
confidence: 96%
See 2 more Smart Citations
“…The Byrne et al (2014) study did not find any effect of the child's gender on parent's underestimation of online risks. The Liau et al (2008) study found that parental knowledge about the adolescents' frequency of internet use was lowest among fathers with regard to their son's internet use. In all the other parent-child gender constellations, a comparable level of parental knowledge was found.…”
Section: Extent Of Parental Knowledgementioning
confidence: 96%
“…Five prior studies like this have been identified, each pointing to a parental underestimation of the child's problematic internet use and potentially harmful experiences. Studies conducted in the US by Cho and Cheon (2005) and in Singapore by Liau et al (2008) found a discrepancy between parents' beliefs about their child's exposure to inappropriate internet content (referring to violent, aggressive and pornographic content) and the child's own reported exposure to such material. Also, the UK results of the EU kids online study (Livingstone and Bober 2004) found that children systematically report higher levels of problematic online experiences as compared to what is perceived by their parents (e.g., visiting pornographic websites or giving out personal information online).…”
Section: Extent Of Parental Knowledgementioning
confidence: 98%
See 1 more Smart Citation
“…Les adolescents qui font un usage régulier d'Internet (Liau et al, 2008) sont de plus en plus exposés à l'offre de JHA en ligne (Welte et al, 2004 ;Van Hamel et al, 2007). Ceci est inquiétant puisqu'il est reconnu que les jeunes seraient plus vulnérables que les adultes en ce qui concerne le développement de problèmes de jeu (Chambers et Potenza, 2003 ;Derevensky et al, 2003 ;Messerlian et al, 2004 ;Huang et Boyer, 2007 ;Messerlian et al, 2007 ;Dickson et al, 2008 ;Hansen et Rossow, 2008 ;Molde et al, 2009).…”
Section: Problématiqueunclassified
“…This issue necessitates further understanding on the factors that contribute to adolescents' growing positive attitude towards online games. Studies show that the time spent playing online games has significantly increased in Malaysia over the last decade (Kapahi et al 2013;Liau et al 2008). Given that adolescents are increasingly spending longer hours of their time on playing online games, parents have started to be more concerned about this issue.…”
mentioning
confidence: 99%